Sedulur Sikep, Syariat, dan Toleransi - Sari, Zeti Nofita (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The Sedulur Sikep community is known as a community rooted in the teachings of Samin Surosentiko in Blora, Central Java, which upholds the values of honesty, simplicity, and peace. In their daily lives, Sedulur Sikep coexists with the Muslim community that applies the principles of Islamic law. The interaction between these two value systems creates an interesting dynamic in the social, legal, and cultural spheres, where the local traditions of Sedulur Sikep negotiate with religious norms without causing significant conflict. The purpose of this study is to understand how the dialectic process between law, religion, and culture takes place in the daily lives of the Sedulur Sikep community, as well as how these values can contribute to the development of social and global harmony. The research method used is empirical with a qualitative approach. Data was obtained through field observations, in-depth interviews with Sedulur Sikep leaders, religious leaders, and the surrounding community, as well as a study of local legal and cultural sources. The results of the study show that Sedulur Sikep is able to maintain their cultural identity while still opening space for dialogue with Sharia values and state law. In conclusion, the harmonious interaction between law and culture in this community reflects a model of tolerance and local wisdom that is relevant for strengthening global harmony in the era of modern multiculturalism